Analisis dan desain sistem informasi manajemen transaksi tabungan pada bank sampah terpadu mina sembada berbasis web - Mahesti Rancaksari; Sri Kusumadewi (Faculty of Industrial Technology Universitas Islam Indonesia, 2017)
At the beginning of its establishment in 2013 Integrated Waste Bank of Mina Sembada operated savings transaction manually, so that sometimes in implementation had errors in data processing. Another problem that the work in the waste bank was a social working, so there was no commissionthat made rarely found someone who willing as an employee in it. For that, we need a system that could minimize the number of employee who could manage all the operations of the waste bank. Therefore, the purpose of this research was to design of management information systems for savings transaction web based to facilitate employee in data filling, data searching, data processing until tothe report in the form of Ledger easily and facilitate members to access savings that has been saved or prospective members who will access information about the latest news and profile of Integrated Waste Bank of Mina Sembada.The results showed that